Respostas

2014-07-23T14:18:10-03:00
A-) 3x + 5y =11
5x-5y=5


| 3x + 5y = 11
| 5x  - 5y = 5   --------------isolar o (x)

5x - 5y = 5
5x = 5 + 5y

      5   + 5y  : 5         1 + y
x = ------------         = ------------------ = 1+y
          5        : 5            1

x = 1+ y ----------------------agora substituit o (x)
3x + 5y = 11

3(1+y) + 5y = 11
3 + 3y + 5y = 11
8y + 3 = 11
8y = 11 - 3
8y = 8
y = 8/8
y = 1---------------------------achar o VALOR  de (x)

x = 1+ y
x = 1 + 1
x = 2

V = { 2; 1}

fazendo a verificação(prova real)

para x = 2
       y = 1
 3x + 5y =11
3(2) + 5(1) = 11
  6   + 5    = 11
         11   = 11
5x-5y=5
5(2) - 5(1) = 5
 10  - 5     = 5
        5     = 5    correto 




b-) a+b=9
a+3b+23 

| a + b = 9
| a + 3b = 23

a + b = 9 ------------------------------isolar o (a)
a = 9 - b-------------------substituir o (a)

    a + 3b = 23 
(9-b) + 3b = 23
9 - b + 3b = 23
-b + 3b + 9 = 23
       2b = 23 - 9
       2b = 14
        b = 14/2
        b = 7 --------------------achar o valor de (a)
a = 9 - b
a = 9 - 7
a = 2 
V= {2: 7}

verificação
para
a = 2
b = 7

a + b = 9 
2 + 7 = 9
     9 = 9

a + 3b = 23
2 + 3(7) = 23
2 + 21   = 23
      23   = 23   correto


c-) m-h=3
m+3h=11

| m - h = 3
| m + 3h = 11

m - h = 3-------------------isolar o (m)
m = 3 + h----------------------------------------substituir o (m)

       m + 3h = 11
(3 + h) + 3h = 11
3 + h + 3h   = 11
+h + 3h + 3 = 11
      4h + 3 =11
      4h = 11 - 3
      4h = 8
       h = 8/4
       h = 2-----------------------achar o valor de (m)

m = 3 + h
m = 3 + 2
m = 5

V = {5: 2}

verificando
para
m = 5
h = 2

m - h = 3
5 - 2 = 3
    3 = 3

m + 3h = 11
5 + 3(2) = 11
5  + 6   = 11
      11  = 11  correto 
1 5 1